HUBUNGAN PELATIHAN DAN MOTIVASI PERAWAT TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT PUSAT TNI AU ANTARIKSA JAKARTA. - I Gusti Ngurah Willy Hermawan; Evaf Maulina (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThere is a positive relationship between training and nurses' work motivation in the inpatient room of the Central Indonesian Air Force Hospital in Jakarta, but between the two there is no mutual influence (not significant). There is a positive relationship between training and the performance of nurses in the inpatient office of the Central Air Force Hospital in Jakarta, but between the two there is no influence (not significant). There is a positive and significant relationship between motivation and performance of nurses in the inpatient room of the Central Indonesian Air Force Hospital in Jakarta.